Elementos fundamentais para uma teoria própria dos contratos de consumo - Lorentino, Sérgio Augusto Pereira (Pontifícia Universidade Católica de Minas Gerais, 2017)
This research named Fundamental elements for an proper theory of consume contracts is the thesis presented to the PhD Program in Private Law, at Pontifícia Universidade Católica of Minas Gerais - PUC Minas. It aims at confirming the impropriety of using the “legal business” to discipline the consumer contracts. Drown on a bibliographic and jurisprudential review, the research is based on the observation that the current Brazilian legal business theory, although being developed after the Federal Constitution, and in the beginning of 21st century, is still supported by the subject’s freedom of actuation, who, as the titleholder of the autonomy, is able to decide for celebrating or not the contracts, as well as shape their content, deriving from this the juridical obligational value. Nevertheless, the study of consumer society shows that, actually, the logic of freedom cannot be applied to consumer relations, especially to the consumer, because he does not act in a market guided by the autonomy power, but by the necessity of showing relation to the products and services needed for a worthy life. Because of that, both, the legal business and contracts’ general theory, is considered inappropriate for ruling consumer contracts. Consequently, the need of a proper theory, capable of recognizing consumer contracts as a distinct phenomenon of the private contracts in general, is presented. In addition, legal mechanisms connected to its peculiarities are shown. An important paradigm, in this sense, is the study of fact contractual relations, due to their typical social behavior, that offers important reflections about the consumer’s behavior on situations like the massive traffic of certain services. In this way, some fundamental elements for creating consumer contracts are approached, based on the presupposition of the consumer contract as the promoter of a human and constitutional functionality, which results, at the end, in a definition of consumer contract, giving it a single capacity of making it different from the lato sensu contract, which is approached by private law.